A study on the genetic variability of stingless bees in Terengganu by using random Amplified Polymorphic DNA (RAPD) markers: a preliminary assessment - Wan Bayani Wan Omar; Wahizatul Afzan Azmi; Shamsul Bahri Abd Razak; Nur Suliyana Mohamad; Nurul Suhadah Ain A. Rahman; Nur Khalilah Azhamshah (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2020)
Heterotrigona itama and Tetragonula fuscobalteata are two common stingless bees species found in Malaysia. Information regarding the application of the molecular technique in genetic variation of the population of these species is very little. The aim of this study is to investigate the genetic variation of the H. itama and T. fuscobalteata by using Random Amplified Polymorphic DNA (RAPD) marker. Eight samples from each species were sampled from Merchang and Kuala Nerus, Terengganu. The extraction of DNA samples based on DNeasy Blood and Tissues Kit from Qiagen. The DNA purity and quality were measured by using BioDrop™µLITE dsDNA. The amplification of the DNA was conducted with OPA-12 and OPA-16 primers for H. itama and OPA-03 and OPA-09 primers for T. fuscobalteata. A total of 18 RAPD bands with 15 polymorphic bands (83%) ranging in size from 350-2500 bp were identified from H. itama. For T. fuscobalteata, 15 bands with 13 polymorphic bands (87%) with sizes ranging from 300-1250 bp. Firstly, the results indicated that the population of H. itama and T. fuscobalteata have high levels of polymorphism due to a low inbreeding factor within their population and the results also revealed that these species have genetic variability. The findings of this study will be used as basic genetic information for stingless bees’ breeding programmes and conservation and management of these species in Malaysia.